Effect of Recombination Catalyst Loading in PEMWE Membranes on Anodic Hydrogen Content Reduction. Issue 12 (1st December 2022) - Abbas, Dunia; Martin, Agate; Trinke, Patrick; Bierling, Markus; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard; Böhm, Thomas
Abstract : Integrating platinum-based recombination catalysts into proton exchange membrane water electrolysis systems effectively reduces the anodic hydrogen content. We studied the effect of the platinum loading of an interlayer close to the anode within the membrane on the anodic hydrogen in oxygen content. For the investigated Pt-loadings between 1 μgPt cm −2 and 140 μgPt cm −2, the results revealed that for a 110 μm membrane, 7 μgPt cm −2 were sufficient to allow a safe operation at cathode pressures up to 10 bar. A further increase of the Pt-loading did not significantly improve the reduction of the anodic hydrogen in oxygen content.